Unraveling swine hepatitis E in the central region of Argentina through ELISA development and epidemiological insights - Gutiérrez, Silvina Elena (2023)
Hepatitis E virus (HEV) is a public health concern globally, causing acute viral hepatitis in humans. Genotype-3 HEV (HEV-3), the most frequently genotype detected in South America, is zoonotic and the main reservoirs are the domestic pig and wild boar. Circulation of HEV-3 in Argentina has been confirmed in humans as well as in pig herds, wild boar and environmental waters. However, data are scarce mainly due to the inaccessibility of serological assays in this country. In order to provide insights in the epidemiology of HEV in swine in Argentina, we developed an indirect ELISA based on the native recombinant protein ORF2 and conducted a serological survey to determine the prevalence of seropositive swine in small-scale pig farms in the central region of Argentina. The method was evaluated in a panel of 157 serum samples, resulting in relative sensitivity of 98.6 % (95 % CI 95 %−100 %) and relative specificity of 97.7 % (95 % CI 94 %−100 %) compared to a commercial test. An almost perfect agreement was obtained between the two tests (Kappa index of 0.961). A survey on 294 samples from 49 small-scale farms resulted in a seropositivity rate of 54 %. Seropositive animals were found in 34 out of 49 (69.4 %) farms. Most of the farms (70.6 %) had over 50 % of seropositive animals. The wide spreading of HEV in the swine population of Tandil, Argentina, underscore the need to better understand the epidemiology of HEV in the region, enabling the implementation of targeted interventions to mitigate the impact of this virus on public health.